Adherence to exercise referral schemes by participants – what do providers and commissioners need to know? A systematic review of barriers and facilitators. (December 2016) - Morgan, Fiona; Battersby, Alysia; Weightman, Alison; Searchfield, Lydia; Turley, Ruth; Morgan, Helen; Jagroo, James; Ellis, Simon
Abstract Background Physical inactivity levels are rising worldwide with major implications for the health of the population and the prevalence of non-communicable diseases. Exercise referral schemes (ERS) continue to be a popular intervention utilised by healthcare practitioners to increase physical activity. We undertook a systematic review of views studies in order to inform guidance from the UK National Institute of Health and Care Excellence (NICE) on exercise referral schemes to promote physical activity. This paper reports on the participant views identified, to inform those seeking to refine schemes to increase attendance and adherence. Methods Fifteen databases and a wide range of websites and grey literature sources were searched systematically for publications from 1995 to June 2013. In addition, a range of supplementary methods including, a call for evidence by NICE, contacting authors, reference list checking and citation tracking were utilised to identify additional research. Studies were included where they detailed schemes for adults aged 19 years or older who were 'inactive' (i.e. they are not currently meeting UK physical activity guidelines). Study selection was conducted independently in duplicate. Quality assessment was undertaken by one reviewer and checked by a second, with 20 % of papers being considered independently in duplicate. Papers were coded in qualitative data analysis software Atlas.ti. This review was reported in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement). Results Evidence from 33 UK-relevant studies identified that support from providers, other attendees and family was an important facilitator of adherence and 'making exercise a habit' post programme, as was the variety and personalised nature of sessions offered. Barriers to attendance included the inconvenient timing of sessions, their cost and location. An intimidating gym atmosphere, a dislike of the music and TV and a lack of confidence in operating gym equipment were frequently reported. Conclusions These findings provide valuable insights that commissioners and providers should consider. The main themes were consistent across a large number of studies and further research should concentrate on programmes that reflect these findings.